Pengaruh Penggunaan Media Powerpoint Terhadap Minat Belajar Bahasa Arab Siswa - Susanti, Elvia; Ritonga, Mahyudin; Bambang, Bambang (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This research aims to determine the influence of power point media towards students' interest in learning Arabic, this goal is based on the problem of low interest students in learning Arabic, the low motivation is according to the hypothesis of the researcher is caused by the inability of teachers to use media that is already familiar with students such as power points. The study used quantitative methods with a test design of the use of PowerPoint on learning in the classroom and seeing its high influence on the students ' Arab learning interests. Data sources of all X-grade students and data analysis techniques using simple recretion assisted with SPSS version 24. Analysis of research data showed: 1) the PowerPoint Medium on Arabic language learning in the high category, evidenced by the median 82.5 2) interest in learning Arabic students was in categories with median 61.7. 3) There is a significant influence of 25.7% by variable X to variable Y, with a value of sig 0.008 and R Square 0.257.